Analysis of the Use of QRIS Transactions and Digital Literacy in Influencing the Income of Culinary MSMEs: JEL Classification: D22, L25, O33, M15, G20 - Serang, Serlin; Lamusu, Moh Fajri R; Iswahyudi, Anugrah; AW, Muh. Aditya (Newinera Publisher, 2025)
The current research is exploring the impact of the QRIS transaction use and digital literacy on the revenue of culinary MSMEs in Makassar City. Based on primary data that constitutes structured questionnaires administered to 50 culinary MSME actors, multiple linear regression analysis will be used in the study to study both individual and combined effects of the variables. Based on the results, QRIS adoption and digital literacy indicated that these two variables have significant positive effects on MSME income. Further, when used simultaneously, these factors have synergetic effect on financial performance. The results indicate that, as QRIS offers an effective and safe transaction platform, it is of the best use when the operators are digitally literate enough to apply the technology to the greater business model. The research will help in MSME digitalization given that it highlights the synergetic nature of using payment technology with human capital capabilities. The implications propose that policy initiatives targeting to enhance the performance of MSMEs in the digital economies should be directed to both access and the enhancement of digital competencies of MSME actors.